Analisis Multi Computer System Menggunakan Framework COBIT 2019 pada Perusahaan Perkakas - Michelle Disa Widjaja; Johanes Fernandes Andry (Diponegoro University, 2023)
The application of information technology is important to help the company's business processes, one of which is a tool company based in Central Jakarta with the main activity of importing and distributing it to shops throughout Indonesia which has implemented IT to assist its business processes. However, based on observations and interviews with the company's directors, the system implemented still has problems that are not suitable for the expectations and needs, such as automatic data updates connected to sales. This research intends to determine the condition and quality of the system used and assess the existing operational implementation using the 2019 COBIT framework with an assessment through capability level, and results of an evaluation used to provide recommendations and suggestions for overcoming existing problems. The process of determining the domain for conducting an audit of the system uses a process of 10 design factors which produces a value of 100 in three domains which means that it has the expected level at level 5 (optimised). The results of the three most important domains for tooling companies based on the process of the design factors that have been carried out are EDM05 (Ensure Stakeholder Engagement), APO14 (Managed Data), and BAI09 (Managed Assets).